Impact of islamic work ethics on corporate social responsibility (CSR) practices among managers of selected public listed companies in Malaysia - Nor Suziwana Hj. Tahir (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
The concept of Corporate Social Responsibility (CSR) has appeared and gained popularity among researchers in Malaysia. It is widely understood as an agenda for the role of business organisations in society and setting appropriate corporate behaviour to comply with. Many previous studies regarding CSR have concentrated on disclosing good corporate practices and the influence of social and cultural differences. However, such research has not as yet been undertaken to study the impact of Islamic work ethics (IWE) in the Malaysian context. To fill this gap, the present study therefore investigated the influence of IWE on CSR practices of Malaysian Public Listed Companies' (PLCs). To further examine whether IWE have an impact on CSR practices by Malaysian PLCs', this study provides empirical evidence based on the survey which was conducted on the executives and managers in randomly selected industries. The findings of this research reveal that there was a positive relationship between IWE and CSR practices. This considered as a recent significant contribution in the field of CSR. Additionally, these aspects are under researched thus proposed further study needed to explore in-depth understanding regarding this issue. The results also indicated that the executives and managers of Malaysian PLCs regardless of their religion, and their perceived CSR benefits had already implemented IWE on CSR practices. Furthermore, the size of the corporations and industries also play an important role in CSR practices of Malaysian PLCs. While acknowledging several implications and limitations of this study, the significant findings uncovered from this study will be a stepping stone to enhance the CSR practices in Malaysia incorporated.